Standard metabolic rate variation among New Zealand Orthoptera - Mariana Bulgarella; John Haywood; Eddy J. Dowle; Mary Morgan-Richards; Steven A. Trewick (Current Research in Insect Science)
Standard metabolic rates (SMR) of ectotherms reflect the energetic cost of self-maintenance and thus provide important information about life-history strategies of organisms. We examined variation in SMR among fifteen species of New Zealand orthopteran. These species represent a heterogeneous group with a wide geographic distribution, differing morphologies and life histories. Gathering original data on morphological and physiological traits of individual species is a first step towards understanding existing variability. Individual metabolic rates of ectotherms are one of the first traits to respond to climate change. Baseline SMR datasets are valuable for modeling current species distributions and their responses to a changing climate. At higher latitudes, the average environmental temperature decreases. The pattern that cold-adapted ectotherms display higher SMR at colder temperatures and greater thermal sensitivity to compensate for lower temperatures and the shorter growing and reproductive seasons is predicted from the metabolic cold adaptation (MCA) hypothesis. We predict higher SMR for the orthopteran species found at higher latitudes. We further compared the index of thermal sensitivity Q10 per species. We used closed-system respirometry to measure SMR, at two test temperatures (4 °C and 14 °C), for the fifteen species acclimated to the same conditions. As expected, we found significant differences in SMR among species. The rate of oxygen consumption was positively correlated with body mass. Our findings do not support the MCA hypothesis. In fact, we found evidence of co-gradient variation in SMR, whereby insects from higher elevations and latitudes presented lower SMR. We discuss our findings in relation to life histories and ecology of each species. The novel physiological data presented will aid in understanding potential responses of these unusual species to changing climatic conditions in Aotearoa/New Zealand.